Divine Love as the Reason for Creation in Islam—An Exploration of Nursi’s Epistles of Light - Rouzati, Nasrin (Religions, 2020)
This paper aims to answer the question “why did God create the world” by examining Bediuzzaman Said Nursi’s magnum opus, the The Epistles of Light (Risale-i Nur), to demonstrate that, from a Nursian perspective, divine love is the raison d’etre for the creation of the world. The first section will investigate the notion of divine love as reflected in the wider Muslim scholarly literature. This will be followed by a discussion on the theology of divine names, with special attention to Nursi’s perspective, illustrating the critical role that this concept plays in Nursian theology particularly as it relates to cosmic creation. The third section will explore the metaphysics of love, the important implications of God’s love in the creation of the world, and its role as the driving force for the dynamism and activities within the structure of the universe. The Qur’anic presentation of love, maḥabba, as well as the significance of the reciprocal nature of love between God and humankind will be explored next. The final section will shed light on the synergy between divine love and the Qur’anic notion of ibtilā, trial and tribulation, to demonstrate its instrumentality in man’s spiritual journey.